DETERMINANTS OF INVESTMENT INTENTION IN GOLD INSTALLMENTS: EVIDENCE FROM ISLAMIC BANKS - Fairuz Fadhilah; Nihayatu Aslamatis Solekah (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
The rapid development of Islamic banking in Indonesia requires the availability of competent human resources and a good understanding of financial literacy. Bank Syariah Indonesia (BSI) responded to this opportunity by launching the Cicil Emas product as a stable investment alternative. However, there is a discrepancy between the results of previous studies regarding the factors that influence investment intention in this program. Therefore, this study examines the effect of financial literacy, trust, service quality, and company image on investment intention in the Cicil Emas program at BSI Malang City. This study uses a quantitative method with a descriptive analysis approach. The sample was selected using a purposive sampling technique with 100 respondents. Data were collected through a Likert-based questionnaire and analyzed using multiple linear regression. The results of the study indicate that financial literacy and service quality have a significant partial effect on investment intention, while trust and corporate image do not have a significant effect. Simultaneously, the four variables of financial literacy, trust, service quality, and corporate image have a significant effect on investment intention, with an R² value of 0.297. This shows that the independent variables in this study are able to explain 30% of the variation in investment intention, while the remaining 70% is influenced by other factors not examined in this study.